YopM inhibits platelet aggregation and is necessary for virulence of Yersinia pestis in mice. - Leung, K Y (1990)
In Yersinia pestis KIM there are 11 Yops (yersinial outer membrane proteins) encoded by the low-Ca2+ response virulence plasmid pCD1. Only YopM and YopN are found in easily detectable amounts in the culture medium. In our previous work, we characterized the yopM gene. In the present study, we constructed a YopM- mutant to elucidate the role of YopM in the virulence of Y. pestis. A lacZYA sequence was inserted 126 base pairs downstream from the start codon of the yopM gene in pCD1. The YopM- mutant had the same growth properties as the parent, Y. pestis KIM5-3001. The inserted lacZ gene was regulated by the promoter of the yopM gene. Accordingly, it was expressed strongly at 37 degrees C in the absence of Ca2+ and was decreased in expression when Ca2+ was present. Northern blot (RNA blot) analysis revealed that the yopM gene was in a monocistronic operon, suggesting that the yopM insertion mutation was unlikely to have polar effects on other genes. The YopM- mutant had strongly decreased virulence in mice, with a 50% lethal dose of 3.4 x 10(5) CFU. Virulence was restored by the cloned yopM-containing 5.5-kilobase HindIII F fragment of pCD1. However, supplying a cloned 1.57-kilobase fragment containing little more than the yopM structural gene caused the yopM mutant to significantly overexpress YopM and failed to restore virulence. The infection kinetics of the YopM- mutant revealed growth in both spleens and livers from days 2 to 4 after infection, followed by a precipitous clearance of the bacteria. YopM-containing supernatant proteins of Y. pestis inhibited thrombin- or ristocetin-induced platelet aggregation, whereas there was no inhibition by supernatant proteins from the YopM- Y. pestis mutant. Accordingly, YopM may prevent platelet-mediated events and serve as an important strategy for the yersiniae in the initial stages of a plague infection.